Wilayah Keagamaan dan Wilyah Kajian Dalam Studi Islam (Jurnal Adabiya, 2020)
Islamic Studies conducted in library of capital city Baghdad and also in Spain where university of Cordoba stand as a center of culture, built by Abdurrahman III from Umayyid Dynasty. Spain and Baghdad continue to compete in education field, that is why cultural centers or Islamic studies centers are located in three palces, Baghdad, Egypt and Spain, Islamic studies in Europe especially in Rumania found a peace situation with local authority, in America, people have high curiosity to know more about Islam, meanwhile in South East Asia, Islam manifested in three ways through trading, missionary endeavor and war